THE DEVELOPMENT OF CHILD SEX EXPLOITATION COMMERCIAL (CSEC) “RESPONSE MODEL IN MEDAN CITY” - Fauzi, Ahmad; Zarzani, T.Riza (Universitas Negeri Medan, 2017)
Abstract The Child of Sex Exploitation Commercial (CSEC) is a fundamental violation of the rights of children. The violation is sexual violence by an adult with a gift to a child, or a third person, or other persons. Simply put, children are treated as sexual and commercial objects. This is a manifestation of forced labor and modern slavery, because not a few children are forced and subjected to physical violence and trauma. The purpose of this study is to examine the legal arrangements for the sexual exploitation of children in Indonesia, to examine and analyze prevention and mitigation of CSEC in Medan City, and to examine barriers to prevention and overcoming of CSEC and how to overcome it. This study uses sociological juridical approach that comes from primary data and secondary data. Data were collected through document studies and interviews conducted to Medan City Center for Childhood Study and Protection (PKPA) staff. The results of the study indicate that the legal arrangement of CSEC in Indonesia is conducted by stipulating several regulations, firstly, Child Protection Act No. 23 of 2002 and the Law on Eradication of Human Trafficking Crime Number 21 of 2007, besides Indonesia has ratified the UN Convention on Human Rights Rights of the Child (CRC) through Presidential Decree No. 36 of 1990. Efforts made to prevent and control the CSEC in Medan City, namely: to socialize in cooperation with various agencies to conduct prevention and prevention of criminal act in the city of Medan CSEC; building networks with various non-governmental organizations and with various institutions to give birth to Regional Regulation (Perda) Number 6 of 2004 on the Elimination of Trafficking in North Sumatra, making efforts of legal advocacy and advocacy from the Prosecutor to the Court; provide assistance to rehabilitate the physical and psychological child victims of CSEC (counseling and medical) and provide safe homes for children. Obstacles in preventing and preventing CSEC in Medan are: legislation that has not been specifically set CSEC, social, economic and psychological factors such as the attitude of community permissive or ignorance of CSEC issues, closed or complicated bureaucracy.Keywords: Efforts, Countermeasures, CSEC